Influence of weeding methods on rhizosphere soil and root endophytic microbial communities in tea plants - Yan, Yuxiao; Wang, Conglian; Wan, Renyuan; Li, Shuang; Yang, Yanfen; Lv, Caiyou; Li, Yongmei; Yang, Guangrong (Frontiers in Microbiology, 2024)
Polyethylene mulch is a kind of inorganic mulch widely used in agriculture. The effects of plastic mulch debris on the structure of plant soil and root growth have been fully studied, but their effects on endophytic microbial communities have not been explored to a large extent. In this study, Highthroughput sequencing of bacterial 16S rRNA genes and fungal ITS region sequences were used to analyze microbial community structure and composition in rhizosphere soil and root endophytic of tea plant under three different weeding methods: polyethylene mulching, hand weeding and no weeding (CK). The results showed that the weeding methods had no significant effect on the rhizosphere and root endophytic microbial abundance, but the rhizosphere bacterial structure covered by polyethylene mulch was significantly different than hand weeding and CK. The rhizosphere fungal diversity was also significantly higher than the other two analyzed treatments. The community abundance of rhizosphere microorganisms Acidobacteria, Candidatus Rokubacteria and Aspergillus covered by polyethylene mulch decreased significantly, whereas Bradyrhizobium, Solirubrobacterales and Alphaproteobacteria increased significantly. The abundance of bacteria Ktedonobacter, Reticulibacter, Ktedonosporobacter and Dictyobacter communities covered by polyethylene mulch was significantly changed, and the abundance of Fusarium and Nitrobacteraceae was significantly increased. Rhizosphere dominant bacteria were negatively correlated with soil available nitrogen content, while dominant fungi were significantly correlated with soil pH, total nitrogen and total potassium. This study elucidated the influence of polyethylene mulch on soil microbial community in tea garden, and provided a new theoretical understanding for weed management.